Stretch of Atrial Myocytes Stimulates Recruitment of Macrophages via ATP Released Through Gap-Junction Channels - Sakiko Oishi (Journal of Pharmacological Sciences, 2012)
Atrial inflammation is critical to atrial fibrillation initiation and progression. Although left atrial dilatation is a risk factor for atrial fibrillation, the mechanism linking atrial dilatation and inflammation is unclear. We evaluated the mechanisms underlying infiltration of macrophages induced by stretch of atrial myocytes. Murine macrophages were co-cultured with HL-1 murine atrial myocyte–derived cells. Mechanical stretch applied to atrial myocytes induced transwell macrophage migration. The gap junction–channel blocker carbenoxolone and the non-specific ATP-signaling modifiers apyrase and pyridoxal-phosphate-6-azophenyl-2′,4′-disulfonate inhibited the enhanced migration. Mechanical stretch of atrial myocytes induced transient increase in extracellular ATP concentration, which was inhibited by carbenoxolone. siRNA knockdown of pannexin-2 inhibited ATP release and macrophage migration. Mice underwent transverse aortic constriction or sham procedure. Transverse aortic constriction procedure induced macrophage infiltration. Daily carbenoxolone administration significantly inhibited macrophage infiltration in the atrium. Thus, mechanical stretch of atrial myocytes induces macrophage migration by ATP released through gap-junction channels, at least in part, in vitro. Administering a gap junction family–channel blocker inhibited this inflammatory change in vivo. Keywords:: atrial fibrillation, inflammation, macrophage, ATP, gap-junction channel